Les Astéries de lIle Inhaca (Mozambique)(Echinodermata, Asteroidea). I. les espèces récoltées et leur répartition géographique. KMMA Annalen Serie IN-8o - Jangoux, M. (Zoologische wetenschappen, 1973)
The collection of Asteroids collected at Inhaca island (Moçambique) contains twelve species : Luidia maculataMüller & Troschel, Astropecten granulatus Müller & Troschel, Astropecten hemprichi Müller & Troschel, Archaster angulatus Müller & Troscher (redescribed), Culcita schmideliana (Retzius), Pentaceraster mammillatus (Audouin), Protereaster lincki (De Blainville), Linckia laevigata (Linné), Linckia multifora (Lamarck), Linckia guildingi Gray, Asterina burtoni Gray and Asterina coronata Von Martens. The geographical distribution of each species is considered.